GAD65 autoantibody positivity and its association with clinical and biochemical parameters among young onset diabetes mellitus: GAD 65 autoantibody positivity in young onset diabetes mellitus (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Despite increasing the prevalence of young-onset (